Physical and Electrochemical Characterization of Functionalized Multiwall Carbon Nanotubes Embedded with Polypyrrole/Gold Nanoparticles - Mutashar, Dhulfiqar S.; Saleh, Wasan R.; Khalaf, Ilham A. X (Iraqi Journal of Science, 2024)
In this study, the indium tin oxide (ITO) electrode was modified, physical and electrochemical characterization were studied to be used in some biosensor applications. Using the drop-casting method, functionalized Multiwall Carbon Nanotubes, Polypyrrole, and gold nanoparticles (f-MWCNTs-AuNP-PPy) were efficiently coated on the surface of an ITO electrode. Fourier transform of infrared radiation (FTIR) and field emission scanning electron microscopy (FE-SEM) were utilized to describe the microscopic structure and morphogenesis of the generated films at the ITO electrode's surface. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used to assess the electroanalytical performance of electrodes after modification. The f-MWCNTs-AuNPs-PPy distribution on the ITO electrode was improved by studying the effect of adding gold nanoparticles and varying polymer concentrations on the film distribution. Electrodes were tested with bare ITO electrodes as well as electrodes modified with f-MWCNTs, f-MWCNTs-PPy, and f-MWCNTs-AuNPs-PPy. The results revealed that nanoparticles distributed on the surface of the modified electrode reduced its impedance by roughly 40% for f-MWCNTs, 75% for f-MWCNTs-PPy, and 95% for f-MWCNTs-PPy-AuNPs. The equivalent circuit was appropriately matched in three situations (f-MWCNTs, f-MWCNTs-PPy, and f-MWCNTs-PPy-AuNPs). The transmission line model, which shows the impedance sensitivity of a diffusion process was utilized to describe the film properties. Nanoparticles enhance electrochemical performance by increasing electrochemical active surface area and allowing electron transport from the redox probe (Ferrocene/ Ferrocenium) to the ITO electrode.